Prevalence and correlates of common mental disorders in people living with HIV in primary health care facilities in Ekurhuleni district - Aniekan Edet; Samuel Agbo; Afolake A. Amodu; Nwabisa N. Edet (African Journal of Primary Health Care & Family Medicine, 2024)
Background: There is paucity of data regarding the prevalence of common mental disorders (CMDs) in people living with HIV (PLHIV) in Ekurhuleni Health District (EHD), South Africa. Also, there is an association between CMDs and poor HIV treatment outcomes. Guidelines therefore recommend that healthcare practitioners screen for CMDs in PLHIV.